Integrated strategies to overcome aluminum toxicity in tropical acid soils - Didy Sopandie (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2025)
Aluminum (Al) toxicity is a major constraint to crop productivity in tropical acidic soils, which predominate in much of Indonesia and other humid regions. This review summarizes advances in understanding Al phytotoxicity, plant tolerance mechanisms, and agronomic, plant breeding, and molecular strategies to overcome Al stress. Plants exhibit two primary adaptation strategies: Al efflux from root tips, with organic acid exudation being crucial (mediated by the ALMT and MATE transporters), and internal detoxification through chelation, compartmentalization, production and activation of antioxidants, osmolytes accumulation, and hormonal regulation. Recent research emphasizes the role of Al receptors, signaling pathways, and regulatory genes such as Nramp and ABC transporters in enhancing Al tolerance. Agronomic strategies, including liming, exogenous compound applications, biostimulants, and beneficial microbes, complement molecular breeding and gene editing approaches such as CRISPR/Cas to develop acid-tolerant cultivars. The success of Brazil and China in conquering acidic soils is attributed to their ability to integrate genomics, physiology, and sustainable agronomic management in transforming acidic soils into productive agroecosystems. Continued collaboration and application of modern biotechnology tools will accelerate the development of crops resistant to Al toxicity, enabling sustainable agricultural productivity in tropical acidic soils. Keywords: Al phytotoxicity; agronomy and crop improvement; research focus and strengths; tolerance mechanisms; ultisols